Narrative Connection: Applying CNSM Theory's Translational Storytelling Heuristic. Issue 4 (1st October 2020) - Kellas, Jody Koenig; Morgan, Toni; Taladay, Cassidy; Minton, Mikki; Forte, Justice; Husmann, Erin
ABSTRACT: Storytelling functions as a means for making sense of and reframing difficulty. The translational storytelling heuristic of communicated narrative sense-making theory proposes that storytelling interventions which facilitate narrative reflection, positive re-framing, and interactional sense-making will positively benefit individuals and families. In this article we describe the process of synthesizing CNSM theory with narrative medicine, narrative theory of identity, and narrative therapy to create a translational storytelling intervention called narrative connection . We then offer a case study using an adaptation of this intervention in the context of parenting. Nine parents in two groups completed the three-week narrative parenting intervention. Preliminary results of the case study suggest that the intervention resulted in an overarching sense of solidarity among parents, facilitates feeling understood, contributes to deeper (self) awareness, and facilitates reassurance, reframing, curiosity, and validation. Overarching benefits included feeling not alone and future plans to be more vulnerable with other parents.